A study on the effects of an explosion in the Pantheon of Rome. (1st June 2018) - Masi, F.; Stefanou, I.; Vannucci, P.
Highlights: Pantheon in Rome. Blast loads simulation. Fluid-structure interaction. Ancient concrete properties discussion. Simulation of structural failure under blast loadings. Abstract: The response of an emblematic monumental structure, the Pantheon in Rome, to an internal blast is addressed. The analysis is a coupled solid-fluid numerical simulation done using JWL equation for the simulation of the blast event and considering the pre-existent cracks in the dome as well as the material nonlinearities of low-tensile strength concrete aggregates. We identify two main phenomena; a focalization of shock waves inside dome-vaulted like structures due to their tendency to concentrate the blast energy and the role played by the pre-existent cracks in the evolution of the structural damage.